Psychological Assessment of Disordered Thinking and Perception. 2021
DOI: 10.1037/0000245-007
|View full text |Cite
|
Sign up to set email alerts
|

Millon Clinical Multiaxial Inventory (MCMI-IV) for assessing disordered thought and perception.

Abstract: T he Millon Clinical Multiaxial Inventory (MCMI) was originally created as the Millon Illinois Self-Report Inventory (MISRI) to measure the prototypes of Theodore Millon's (1969) personality theory. Shortly thereafter, the MISRI was expanded to include other diagnostic entities besides personality, and it lost the Illinois part in its title when Millon moved to the University of Miami (Millon, 1977). Millon believed that neither his theory nor his test should remain static, and the current version of the test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The MCMI-IV consists of 195 true-false self-report items (Millon et al, 2015). Of these, I (Choca, 2021) found that 122, or 70% of the items, were taken from its predecessor, the MCMI-III (Millon, 1983). Outside of what appears in the MCMI-IV Manual, there was little published data on the newer version at the time of this writing.…”
Section: Bsds and The Mcmi-ivmentioning
confidence: 99%
“…The MCMI-IV consists of 195 true-false self-report items (Millon et al, 2015). Of these, I (Choca, 2021) found that 122, or 70% of the items, were taken from its predecessor, the MCMI-III (Millon, 1983). Outside of what appears in the MCMI-IV Manual, there was little published data on the newer version at the time of this writing.…”
Section: Bsds and The Mcmi-ivmentioning
confidence: 99%